PSIKOEDUKASI PERAN GURU DAN ORANGTUA DALAM MEMBERIKAN PENDIDIKAN SEKSUAL - Rahma, Selvi Alivia; Nurhidayah, Siti (An-Nizam, 2023)
The Indonesian Federation of Teachers' Unions noted that 46.67% of sexual violence cases during January-April 2023 occurred at the SD / MI level. This is because the teaching of sexual education is still taboo to be discussed or taught in formal education even though it has an important influence on child development. In Bantarjaya Village itself, this is still lacking attention due to the lack of knowledge for the community regarding sexual education. For this reason, researchers conducted teaching through discussion methods, interviews, roleplay on how to communicate well on how to convey topics about sexual education to children and psychoeducation to parents and teachers who as adults have an important role and are responsible for guiding children in sexual education to avoid deviation. The result is that despite the lack of knowledge obtained by parents and teachers, they still know at least a little about the boundaries that must be maintained (should not be touched) that refer to religious teachings.